Islam and the West - Lewis, Bernard, 1916-2018 (Oxford University Press, 1993)
Hailed in The New York Times Book Review as "the doyen of Middle Eastern studies," Bernard Lewis has been for half a century one of the West's foremost scholars of Islamic history and culture, the author of over two dozen books, most notably The Arabs in History, The Emergence of Modern Turkey, The Political Language of Islam, and The Muslim Discovery of Europe. Eminent French historian Robert Mantran has written of Lewis's work: "How could one resist being attracted to the books of an author who opens for you the doors of an unknown or misunderstood universe, who leads you with.